Inspiration and Digitization Strategy for Minority Muslim Women Entrepreneurs in MSMEs: Case Study of Nepal - Saemah Shamim (Al-Muraqabah: Journal of Management and Sharia Business, 2022)
This article is based on research into the growth of women entrepreneurs in Nepal, with a focus on motivation to start small firms and digitalization methods in their operations. The study was based on a review of the literature and a short field survey of women who own small enterprises (MSMEs) in Kathmandu. Many respondents claimed that their initial purpose in starting their enterprises was to earn more revenue in finance, as per the data from the interviews. As seen, dealing with digitization is an issue that cannot be ignored as an entrepreneur in the new normal period i.e., after the Pandemic. To improve its business operations and income, it implemented a number of changes and tactics. They were optimizing digital marketing, discovering commercial prospects, developing new markets, and putting the marketing strategy into action.